Family planning choice behaviour in urban slums of Bangladesh: An econometric approach - Abul Barkat; Mati Ur Rahman; Manik Lal Bose (Asia-Pacific Population Journal, 1997)
Policy measures, in their dimensions, urgency and intensity, should differ between Bangladesh’s metrocities.